PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU MTs DI KECAMATAN WINONG KABUPATEN PATI - Sa’dun, 12.52.02.0212; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of intrinsic motivation and Professional Competence on the performance of teachers in Winong Islamic Junior High School Pati regency moderated with organizational culture. The specific objectives of this study was to examine the effect of intrinsic motivation and professional competence on the performance of teachers who are moderated by the role of organizational culture. The usefulness of this study is to clarify and extend previous research on the effect of intrinsic motivation and professional competence on the performance of teachers who moderated the organizational culture. This study used a population of teachers in Winong Islamic Junior High School Pati regency much as 173 teachers. Sampling techniques in this study is non probabilty sampling with proporsional sampling method. The method used in this research is multiple regression with difference quasi moderation. Based on the results of the study can be summarized as follows intrinsic motivation does not affect the performance of teachers, professional competence has a positive and significant affect the performance of the teacher, organizational culture has a positive and significant affect the performance of the teacher, the influence of intrinsic motivation on teacher performance does not moderated by organizational culture, and the influence of professional competence on performance teachers does not moderated by organizational culture. Keywords: intrinsic motivation , professional competence, organizational culture, performance teacher and moderation